Academic writing skills in the eyes of university students of English and their teachers - Wolanin, Agata (Glottodidactica, 2025)
Developing academic writing skills can often be seen as daunting, both for students and teachers, despite the fact that writing academic texts is an indispensable part of academic achievement. This problem, however, has not been sufficiently addressed in the literature. Thus, the main aim of the study was to explore the English philology university students’ and their teachers’ beliefs regarding academic writing skills in general and their experiences with writing academic texts in particular, as well as their attitudes toward the subject itself. The secondary aim was to see to what extent the students’ opinions correspond with their teachers’ perspective. There were three research questions: (1) What is the English students’ attitude towards academic writing in general? (2) What do the students expect from an academic writing course? (3) What is the English teachers’ perspective on and experience with teaching academic writing? In an effort to answer these questions a diagnostic survey was administered to both English university students (N = 67) and their teachers (N = 15), inquiring about their beliefs, experiences and attitudes. The results confirmed the hypothesis that academic writing is a challenging subject for both students and teachers alike – while the teachers struggle with formulating clear and viable objectives, the students struggle with a number of issues, from text analysis to motivation. In general, the attitudes toward academic writing can be classified as predominantly negative. The results of this mini-project are hoped to give a better insight into the needs and attitudes of both English students and their teachers towards academic writing and might help in identifying possible room for improvement in teaching academic writing skills.